Legal Protection of Women Victims of Revenge Porn Based on Pornography and ITE Law - I Putu Ngurah Santi Juni Dwi Adnyana; Titiek Guntari (IHSA Institute, 2022)
Revenge porn is a form of coercion, threat to someone, generally female, to spread pornographic content in the form of photos or videos. The perpetrator could be his boysfriend, ex-boyfriend who wants to come back, or unidentifiable person. As a result of these actions the victim suffers immaterial losses in the form of psychological pressure and exclusion from society. Law enforcement is important to protect victims. KUHAP as a regulation regarding the judicial process must pay attention to the rights of victims. This research uses normative legal research, by looking at the current norms. Data collection is done by literature study namely by looking for regulations, and theories from books journals and research results. The problem in this study is how the legal arrangements in Indonesia are related to the phenomenon of Revenge Pornography?. And How Legal Protection for Women Victims of Revenge Pornography?. The results of this study indicate that the legal arrangements regarding revenge porn which are regulated in the Pornography Law and the ITE Law are only criminal acts and criminal threats, and catch criminals. However, legal protection for women victims of revenge porn is not regulated in the Pornography Law and the ITE Law. Regarding the protection of women victims of revenge porn so far it has not been regulated in the Pornography Law and the ITE Law and in judicial practice, legal protection of the victim is considered sufficient by imposing a sentence on the perpetrator. Whereas the protection of women victims of revenge porn should protect the dignity of the victims, the honor of the victim and the psychological aspects of the victim or the victim's psychology.